Contribution of Islamic Banking Towards Economic Growth in Indonesia With Data Panel Regression Approach - Dukalang, Hendra H.; Ningsih, Setia (Fakultas Ekonomi dan Bisnis Islam _ IAIN Sultan Amai Gorontalo, 2024)
This study uses a panel data regression approach to analyze the contribution of Islamic banking to economic growth. The variables in this study consist of one dependent variable and three independent variables. The dependent variable is Economic Growth Income. while the independent variable consists of 3 variables, namely: Total assets, third party funds and Islamic financing. The population and samples used in this study were all provinces in Indonesia in 2014-2020. In this study, the panel data regression models used are the Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM). Selection of panel data regression estimation models using tests, namely the Chow Test and the Hausman Test. Based on the statistical methods used, the best model is obtained with the random effect model. The Fixed effect model above has an R-squared of 0.4742 or in other words the predictor variable is able to explain 47.42% of the response variable.